What to Know about Food Flavor? A Review - Al Saqqa, Ghada S. R. (Jordan Journal of Agricultural Sciences, 2022)
The primary function of flavors is to add taste or aroma to foods, as they have no nutritional properties. According to Flavor and Extract Manufacturers Association (FEMA), flavors have a place in the food supply to meet consumer demand for a variety of safe and tasty products. This review provides an overview of the three flavor groups; natural flavors, nature-identical flavors, and artificial flavors, where they are added to replace the flavor lost through processing and to develop new products, while flavor enhancers are compounds with no intrinsic aroma or taste of their own, but when are added in low concentrations to appropriate foods, they improve the palatability of the food distinctly, a popular example is monosodium glutamate. The food industry is constantly striving to improve the quality and taste of modern food products through creating new flavors and improving existing ones. The flavors of commercially produced food products are usually created by florists who work for flavor companies. Among these commercial flavors are those that are often added to elderly food to offset the losses in their sense of smell and taste. Encapsulation can be used to treat flavors and protect them from evaporation, reaction, or disappearance from food. Flavors manufacturers need to know which ingredients are allowed in the community that includes restrictions and specific requirements for use in food applications.